Utilization and clinical outcomes of sacubitril/valsartan in Sudanese heart failure patients: A multicenter cross-sectional study - Alanood Elnaeem Mohamed; Toga K. Mohamed; Bashir A. Yousef; Yaman Walid Kassab; Kannan O. Ahmed (Pharmacia)
Sacubitril/valsartan (Sac/Val) is a cornerstone therapy for heart failure with reduced ejection fraction (HFrEF), yet its real-world use remains poorly described in Sudan. This multicenter, cross-sectional study aimed to evaluate Sac/Val utilization patterns and clinical outcomes among 170 Sudanese patients. The mean patient age was 61 years, and 77.6% of patients found Sac/Val unaffordable. Additionally, 92.4% lacked insurance coverage. Most patients (62.4%) were de novo users, 78.8% initiated Sac/Val at 50 mg BID, 71.8% underwent up‑titration, and only 36.5% achieved the target dose of 200 mg BID. Notably, longer treatment duration was significantly associated with higher hospitalization rates (p = 0.003), while achieving the target dose correlated with improved ejection fraction (p = 0.045). Despite guideline-based initiation and titration, target dose achievement remains suboptimal. Socioeconomic barriers predominate, limiting treatment optimization. These findings highlight an urgent need for policymakers to integrate Sac/Val into national insurance programs and improve its affordability.